OPTIMALISASI SISTEM PEMBELAJARAN DARING TARUNA KOMUNIKASI PENERBANGAN PADA MATA KULIAH AFIS DI POLITEKNIK PENERBANGAN SURABAYA - Anita Farah Subagya; Fatmawati; Siti Nurfadhilah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In implementing education to produce competent and professional graduates, the Aviation Communication Study Program requires a good learning system. While carrying out online learning activities, teaching and learning activities are carried out via Zoom Meetings, this is less effective because the implementation of the practicum cannot run optimally. On the other hand, the ability of cadets to receive material is also different. The research method that the author uses is descriptive qualitative with data collection methods Observation, Questionnaire, Literature Study and Interview. The questionnaire method uses 42 populations of KP 5 cadets with a total of 10 questions. While the interview method uses 6 resource persons consisting of 2 lecturers and 4 KP 5 cadets. From the data obtained through this research, it is known that, in optimizing the online learning system in AFIS courses, supporting applications are needed in its implementation. The application in question can facilitate lecturers and cadets in the online learning process. The implementation of the practicum will also be easier if there are adequate online learning support facilities.